Regional Schedule of Vaccination in Moscow: History, Development, Prospects - O. V. Filippov; L. N. Bolshakova; T. N. Elagina; Yu. B. Novikova; R. F. Shapovalova; A. M. Aristova (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. The Russian Federation is one of the largest states in the world, includes 85 subjects of the Federation located in two hemispheres of the Earth (Western and Eastern). The geographical location of the country, as well as the differences in territories according to the epidemiological situation, allow each subject, in accordance with the law, to develop regional schedules of vaccination. Aim. To analyze the trends in improving the regional schedule of routine vaccination, as well as to outline the directions of its development. Materials and methods. The analysis of regional schedules of vaccination in different years, including a descriptive stage based on the study of regulatory documents for the period from 2001 to 2019, was carried out. Results. The regional vaccination schedule was first introduced in Moscow in 2001. Infectious diseases against which vaccination was carried out, basically repeated the National calendar. Over time, the Regional Schedule has changed depending on the epidemic and economic situation in the capital. For the period from 2001 to 2019, the calendar had 4 editions - the number of infections against which residents of Moscow are vaccinated increased from 10 infectious diseases to 17. Vaccination schemes also undergo changes: the age of measles and mumps booster vaccination, the tactics of vaccination against viral hepatitis B, the introduction of combined vaccines, as well as changes in composition persons at risk to be vaccinated. The stages of introducing vaccination against rotavirus infection, meningitidis, pertussis, human papillomavirus infection, varicella, viral hepatitis A, pneumococcal infection into the Regional Schedule are described. A brief overview got of the regional schemes of vaccinations in some regions of the Russian Federation. Conclusion. The article describes an almost 20-year history of improving the Regional Schedule of Routine Vaccination in Moscow in the context of the development of the National Schedule of Routine Vaccination of the Russian Federation, as well as in comparison with immunization calendars from other countries of the world and constituent entities of the Russian Federation. Achievements and directions for further improvement of the Regional schedule of preventive vaccinations in the city of Moscow are indicated.